An RNA Binding Protein Negatively Controlling Differentiation in Fission Yeast - Tsukahara, Kappei (American Society for Microbiology, 1998)
The fission yeast Schizosaccharomyces pombe starts sexual development when starved for nutrients and simultaneously activated by mating pheromones. We have identified a new gene regulating the onset of this process. This gene, called nrd1(+), encodes a typical RNA binding protein that preferentially binds poly(U). Deletion of nrd1(+) causes cells to initiate sexual development without nutrient starvation. We have found that the biological role of nrd1(+) is to block the onset of sexual development by repressing the Ste11-regulated genes essential for conjugation and meiosis until cells reach a critical level of starvation.